2008
DOI: 10.1021/ac8005439
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Immunogenicity in the Presence of Excess Protein Therapeutic Using Immunoprecipitation and Quantitative Mass Spectrometry

Abstract: The administration of biological protein therapeutics can lead to an unwanted immune response resulting in the generation of anti-drug antibodies (ADA) with potentially harmful clinical consequences. Hence, to develop safe and efficacious biotherapeutics, the immunogenic potential needs to be examined during the development phase. Current assay technologies measuring ADAs are subject to interference by high circulating concentrations of the protein therapeutic, raising concerns about data reliability since pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Although the original SISCAPA work relied on online nanoliter immunoaffinity columns based on Poros supports linked to nanoflow LC and nanospray mass spectrometry (6 ), off-line magnetic bead-based enrichment of enzymatically released peptides followed by either nano-or capillary LC-MS/MS has become a popular approach (7)(8)(9)(10)(11)(12). Bead-based sample preparation has the advantage that the antibody capture step can be done in parallel for multiple samples, and this process can be automated on a magnetic particle processor (11 ) or liquid-handling robotics, as shown for immunoaffinity enrichment of proteins (13,14 ). An extension of the magnetic bead SISCAPA work is the use of an inline bead-trap device to allow the quantification of lower-abundance peptides in a more automated fashion and with reduced off-line handling (15 ).…”
mentioning
confidence: 99%
“…Although the original SISCAPA work relied on online nanoliter immunoaffinity columns based on Poros supports linked to nanoflow LC and nanospray mass spectrometry (6 ), off-line magnetic bead-based enrichment of enzymatically released peptides followed by either nano-or capillary LC-MS/MS has become a popular approach (7)(8)(9)(10)(11)(12). Bead-based sample preparation has the advantage that the antibody capture step can be done in parallel for multiple samples, and this process can be automated on a magnetic particle processor (11 ) or liquid-handling robotics, as shown for immunoaffinity enrichment of proteins (13,14 ). An extension of the magnetic bead SISCAPA work is the use of an inline bead-trap device to allow the quantification of lower-abundance peptides in a more automated fashion and with reduced off-line handling (15 ).…”
mentioning
confidence: 99%
“…Our goal was to determine whether the ADA samples were positive or negative, and the spiking experiment should serve the purpose. It has been reported that 100 μg/mL of hGHA was sufficient to convert 100 μg/ mL ADA to hGH-ADA complex in human serum [21]. In the immunopurification process, the mouse mAbdrug-ADA complexes were separated from the plasma by a magnet and any endogenous monkey plasma proteins that bound non-specifically on the beads were subsequently washed off.…”
Section: Resultsmentioning
confidence: 99%
“…With traditional ADA immunoassay, only drug-free or partially drug-free ADA can be detected, and the presence of high drug levels in study samples can interfere with the detection of ADA, especially in bridging assay formats. Drug tolerance which is generally defined as the maximal amount of free drug in the samples that still allows detection of ADA at an acceptable sensitivity, may be improved using various approaches including the use of excess spiked drug to create and detect drug-ADA complexes rather than free ADA [18][19][20][21]. LC/MS has been used to assess ADA in the presence of excess protein therapeutic in support of clinical programs addressing the safety and tolerability of human growth hormone analogues [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PK parameters remain an integral component of clinical development so it is important to select ADA and PK time points at pre-dose and trough circulating drug concentrations, and preferably after an appropriate drug washout period (8), to truly understand the impact of ADA on the PK and ensure there is minimum interference in the PK assay. Although PK sample time points are typically more numerous than ADA sampling, it is important to have some PK and ADA sampling points at the same time to truly understand the impact of the ADA on PK.…”
Section: Nonclinical and Clinical Study Samplesmentioning
confidence: 99%